A survival case of amlodipine poisoning (Indian Journal of Case Reports, 2020)
Calcium channel blockers are commonly used in various cardiovascular diseases, but its poisoning may lead to fatal outcomes. We report a case of alleged poisoning of amlodipine in a 25-year-old female who consumed 20 tablets of 5 mg amlodipine. She presented with cardiogenic shock, hypoglycemia, hypokalemia, constipation, and central nervous system symptoms which were managed with intravenous crystalloids, calcium gluconate, 5% dextrose, dopamine, and noradrenaline infusion after which patient responded well and discharged.